Design and performance evaluation of a solar tracking panel of single axis in Colombia (2021)
This paper presents the mechanical design of a single axis solar tracking system, as well as the electronic design of a system that to record in real time the electric power delivered by the solar tracker and to evaluate its performance. The interface was developed in Labview and it compares the power supplied by the tracker with the power supplied by static solar panel of the same characteristics. The performance is initially simulated using Pv-Syst software, and later validated with the data obtained by the interface. As a result, the use of the solar tracker increases the power delivered by a minimum of 19%, and it can go as high as 47.84%, with an average in increase in power of 19.5% in the monthly energy production. This experimental result was compared with the simulation by Pv-Syst software and shows a difference of only 2.5%, thus validating the reliability of the simulation. This behavior pattern coincides with previous studies carried out for equatorial latitudes.